RISE OF ISLAM IN KASHMIR VALLEY - Dr. Shabir Ahmad Lone; Mohammad Ishaq Lone; Dr. R. Abida Begum; Dr. Hilal Ahmad Parray (CV. Radja Publika, 2026)
Kashmiri Muslims are an ethnic group native to the Kashmir Valley in Indian-administered Kashmir, predominantly adhering to Sunni Islam. They refer to themselves as